Longitudinal splitting versus sequential unzipping of thick-walled carbon nanotubes: Towards controllable synthesis of high-quality graphitic nanoribbons. (December 2016) - Yang, Ming; Hu, Liguo; Tang, Xingwei; Zhang, Hongdi; Zhu, Hanxing; Fan, Tongxiang; Zhang, Di
Abstract: Despite significant efforts to develop ways to produce customized carbon-based nanostructures, facile synthesis of mass graphene/graphitic nanoribbons (GNRs ) without losing the intrinsic sp 2 -structure and properties remains challenging. Here we report that bulk of multi-layered graphitic nanoribbons can be prepared by gas-phase oxidative splitting of multi-walled carbon nanotubes (MWCNTs ) using HNO3 vapor. The longitudinal splitting behavior of MWCNTs is substantially dependent on three key factors: the utilization of gaseous oxidant, the use of highly-crystallined carbon nanotubes with larger diameter, and the associated high-pressure conditions. Moreover, this splitting process is evidenced to be edge-selective and nonaggressive as opposed to traditional wet chemical oxidation, for which the obtained GNRs show minimized oxidation level, highly intact crystalline and robust electrical conductance. This study suggests a simple yet effective strategy for producing mass high-quality GNRs.